2000
DOI: 10.1152/jappl.2000.89.2.493
|View full text |Cite
|
Sign up to set email alerts
|

Increased vasoconstrictor sensitivity in obstructive sleep apnea

Abstract: We studied vasoconstrictor sensitivity and cholinergic responsiveness of the forearm vasculature in 10 male patients with obstructive sleep apnea (OSA) and 10 healthy controls. Subjects with regular medication, known arterial hypertension, diabetes mellitus, or dyslipidemia were not included in this study. Age, body mass index, blood pressure, blood glucose, serum lipids, and baseline forearm vascular conductance (derived from venous occlusion plethysmography and intra-arterial blood pressure measurement) did … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
67
1
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(72 citation statements)
references
References 39 publications
3
67
1
1
Order By: Relevance
“…81 However, other studies using correlative approaches in patients with comorbidities reported an inverse relationship between brachial artery flow-mediated dilation and sleep apnea severity. 104 Conflicting findings with regard to resistance vessel endothelial function in OSA 105,106 speak to the importance of careful exclusion of comorbidities in studies of OSA patients. Nevertheless, recent data suggest not only that conduit vessel endothelial function may be impaired in OSA but also that the impairment may be related to endothelial cell apoptosis and that treatment with CPAP may improve endothelial function.…”
Section: Endothelial Dysfunctionmentioning
confidence: 99%
“…81 However, other studies using correlative approaches in patients with comorbidities reported an inverse relationship between brachial artery flow-mediated dilation and sleep apnea severity. 104 Conflicting findings with regard to resistance vessel endothelial function in OSA 105,106 speak to the importance of careful exclusion of comorbidities in studies of OSA patients. Nevertheless, recent data suggest not only that conduit vessel endothelial function may be impaired in OSA but also that the impairment may be related to endothelial cell apoptosis and that treatment with CPAP may improve endothelial function.…”
Section: Endothelial Dysfunctionmentioning
confidence: 99%
“…Several studies have proposed impaired vasodilation as a likely contributor to high blood pressure in OSAS patients [13,36]. This work should be interpreted with caution, since many confounding factors (e.g.…”
Section: Sleep-related Disordersmentioning
confidence: 80%
“…It has been shown that chronic hypoxia decreases vascular sensitivity to vasoconstrictors, 33,34 so that elevated ET-1 levels under that setting may not stimulate increased systemic blood pressure. In contrast, sleep apnea has been associated with increased vasoconstrictor responses 6,35 and decreased vasodilator responses. 6 Therefore, increased vascular reactivity coupled with elevated circulating ET-1 may contribute to the pathogenesis of IH-induced hypertension.…”
Section: Kanagy Et Al Intermittent Hypoxia and Endothelin 513mentioning
confidence: 97%